Social transformation and the global economy : labour, Latin America and the Lefts - Munck, Ronaldo (Routledge, 2024)
"The overall context of this book is set by the decline of the globalization paradigm's ability to grasp the complexity and uncertainty of the current era. It takes a new approach based on the frame of 'transformation' viewed as a catalyst to understand the complex interconnected nature of the world around us from a concrete, grounded perspective. Labour or work is still what makes the world go round and Latin America offers a unique laboratory of social transformation, since the 'pink tide' of the 2000s. The left it refers to, is a new non-dogmatic version that does not just recycle old debates but, rather, opens up new perspectives. The book is at once global in its ambition while grounded in labour and Latin American realities. Theoretically based and empirically robust, it will enthuse the reader to pursue their own research on matters covered here. Part I deals with several key debates around labour including the emergence of a precariat, from a standpoint that foregrounds labour agency but also the view from the South, that is the majority world. Part II takes up various debates around contemporary Latin America from a cultural political economy perspective with an emphasis on the dynamics of social transformation. Part III explores the contributions from the broadly defined left towards an understanding of the current challenges faced by those seeking an alternative to the status quo in Latin America and beyond. Providing a theoretically sophisticated yet readable text on key contemporary issues, this fully interdisciplinary book will find a broad audience among researchers, scholars and advanced students of labour, Latin American and development studies, economics, sociology and politics"-- Provided by publisher.
Keywords: Economic development -- Social aspects -- Latin America.; Labor -- Latin America.; Social change -- Latin America.; Latin America -- Social conditions.; Latin America -- Economic conditions.; elektronické knihy; electronic books